Superabsorbent food packaging bioactive cellulose-based aerogels from Arundo donax waste biomass. (November 2019) - Fontes-Candia, Cynthia; Erboz, Evrim; Martínez-Abad, Antonio; López-Rubio, Amparo; Martínez-Sanz, Marta
Abstract: A. donax waste biomass has been valorized for the extraction of cellulosic fractions with different purification degrees, as well as aqueous bioactive extracts, which were then combined to develop superabsorbent bioactive aerogels. All the developed aerogels presented excellent water and oil sorption capacities; however, the presence of hemicelluloses yielded more porous and hydrophilic aerogels, capable of absorbing more water. With regards to the aqueous extracts, the hot water treatment (HW) of A. donax stems promoted the extraction of polysaccharides and polyphenols, producing the extract (S-HW) with the highest antioxidant capacity. This extract was then incorporated into the aerogels produced from the less purified stem fractions (F2A and F3A), which were chosen due to their good water sorption capacity, higher antioxidant potential and lower production costs and environmental impact. The hybrid aerogels showed a great potential to be used as bioactive pads for food packaging. In particular, the F2A + S-HW aerogel would be the most optimum choice since it provides a complete release of the extract in hydrophilic media, as demonstrated by in-vitro release and β-carotene bleaching inhibition studies, and it is able to reduce the colour loss and lipid oxidation in red meat upon refrigerated storage to a greater extent. Graphical abstract: Image 1 Highlights: Cellulosic fractions extracted from A. donax biomass produced superabsorbent aerogels. Fractions containing hemicelluloses produced more hydrophilic and porous aerogels. Extracts with the highest antioxidant capacity were obtained by a heating treatment. Selected aerogels provided a complete release of the extract in hydrophilic media. Hybrid aerogels reduced oxidation processes in red meat upon storage.